ANALISIS KUALITAS AIR PADA KOLAM PENDEDERAN IKAN LELE DUMBO (Clarias gariepinus) DENGAN PENAMBAHAN TEPUNG DAUN SINGKONG (Manihot utillisima) SEBAGAI PAKAN BUATAN - Andi Alifia Fara Dhiba; Husain Syam; Ernawati Ernawati (Jurnal Pendidikan Teknologi Pertanian, 2022)
This study aims to determine the effect of artificial feed by adding cassava leaf flour (Manihot utillisima) to the water quality of the African catfish nursery pond (Clarias gariepinus). This study used the T test (one sample T test) to compare the treatment with artificial feed and commercial feed consisting of 3 replications. The feeding dose was 3% of the weight of the fish for 30 days of maintenance with the frequency of feeding twice a day. Parameters observed were NH3, NO2, NO3, pH, temperature, DO and survival of African catfish. The results showed that the provision of artificial feed in the African catfish nursery did not have a significant effect (P> 0.05) on the observed water quality parameters. The quality of water obtained during maintenance by providing commercial and artificial feed is still supporting the survival of African catfish.